Does contrast between eggshell ground and spot coloration affect egg rejection? - Dainson, Miri; Hauber, Mark E; López, Analía V; Grim, Tomáš; Hanley, Daniel (Die Naturwissenschaften, 2017)
Obligate avian brood parasitic species impose the costs of incubating foreign eggs and raising young upon their unrelated hosts. The most common host defence is the rejection of parasitic eggs from the nest. Both egg colours and spot patterns influence egg rejection decisions in many host species, yet no studies have explicitly examined the role of variation in spot coloration. We studied the American robin Turdus migratorius, a blue-green unspotted egg-laying host of the brown-headed cowbird Molothrus ater, a brood parasite that lays non-mimetic spotted eggs. We examined host responses to model eggs with variable spot coloration against a constant robin-mimetic ground colour to identify patterns of rejection associated with perceived contrast between spot and ground colours. By using avian visual modelling, we found that robins were more likely to reject eggs whose spots had greater chromatic (hue) but not achromatic (brightness) contrast. Therefore, egg rejection decision rules in the American robin may depend on the colour contrast between parasite eggshell spot and host ground coloration. Our study also suggests that egg recognition in relation to spot coloration, like ground colour recognition, is tuned to the natural variation of avian eggshell spot colours but not to unnatural spot colours.
Keywords: Chroma; Spectrometry; American robin; Spot coloration; Egg Shell; ovum; Ovum; Songbirds; Animals; Brood parasitism; zpěvní ptáci; Egg rejection; vaječná skořápka; hnízdění; zvířata; Nesting Behavior